The Impact of Program Structure and Goal Setting on Mentors’ Perceptions of Peer Mentorship in Academia - Haqqee, Zeeshan; Goff, Lori; Knorr, Kris; Gill, Michael B. (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2020)
Many peer mentorship programs in academia train senior students to guide groups of incoming students through the rigors of postsecondary education. The mentorship program’s structure can influence how mentors develop from this experience. Here, we compare how two different peer mentorship programs have shaped mentors’ experiences and development. The curricular peer mentorship program was offered to mentors and mentees as credited academic courses. The non-curricular program was offered as a voluntary student union service to students and peer mentors. Both groups of peer mentors shared similar benefits, with curricular peer mentors (CMs) greatly valuing student interaction, and non-curricular peer mentors (NCMs) greatly valuing leadership development. Lack of autonomy and lack of mentee commitment were cited as the biggest concerns for CMs and NCMs, respectively. Both groups valued goal setting in shaping their mentorship development, but CMs raised concerns about its overemphasis. Implications for optimal structuring of academic mentorship programs are discussed.